2022
DOI: 10.11604/pamj.2022.41.322.29734
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for caesarean delivery and fetal macrosomia among women with gestational diabetes in Nyeri County, Kenya: a cross-section study

Abstract: Introduction gestational diabetes mellitus is an emerging global public health threat due to adverse health outcomes. This study aimed to determine the risk factors for caesarean delivery and macrosomia among women with gestational diabetes in Nyeri County, Kenya. Methods this study used a cross-section design. Randomly, 152 women with gestational diabetes and attending antenatal clinics and maternity were enrolled in this study. Data was collected using a questionnaire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 37 publications
3
6
0
Order By: Relevance
“…We found that pregnant women with pregnancies complicated with GDM tend to have advanced age and that advanced maternal age increased the likelihood of having GDM. This nding is in agreement with studies from various countries globally that demonstrated an association between GDM and advanced maternal age [4,12,15,16]. This is probably due to the fact that mothers with advanced maternal age have given birth severally, pregnancy is known to initiate metabolic disorders such as increased insulin resistance and may result in obesity [2].…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…We found that pregnant women with pregnancies complicated with GDM tend to have advanced age and that advanced maternal age increased the likelihood of having GDM. This nding is in agreement with studies from various countries globally that demonstrated an association between GDM and advanced maternal age [4,12,15,16]. This is probably due to the fact that mothers with advanced maternal age have given birth severally, pregnancy is known to initiate metabolic disorders such as increased insulin resistance and may result in obesity [2].…”
Section: Discussionsupporting
confidence: 91%
“…One of the most common non-communicable metabolic deregulation that present as glucose or carbohydrate intolerance of differing severity detected at the start or during pregnancy is Gestational Diabetes Mellitus (GDM) [1]. It is a common pregnancy complication accounting for 90% of all pregnancy complicated by diabetes [2,3], associated with poor neonatal and maternal outcomes and poses a signi cant health risk for both the mother and neonates [4,5]. In 2013, the World Health Organization (WHO) adopted the International diagnostic and screening criteria for GDM that include performing oral glucose tolerance test (OGTT) in a fasting state [1,6].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations